2020
DOI: 10.5334/aogh.2636
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Undernutrition among At-Risk Children in Neonatal Follow-Up Clinic in Rwanda

Abstract: Background: Sufficient knowledge of the disproportionate burden of undernutrition among vulnerable children is required for accelerating undernutrition reduction in low-income countries. Objectives: We aimed to assess the prevalence of stunting, underweight and wasting and associated factors among high-risk children born preterm, with low birth weight or other birth and neurodevelopmental injuries, who received nutritional support and clinical care follow-up in a Pediatric Development Clinic (PDC) in rural Rwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There is also limited knowledge on feeding practices for small and sick newborns, who are at greater risk for feeding difficulties and malnutrition [46]; limited skills and time for health workers to provide counseling that allows for "trial and error" of different interventions [47]; and limited use of existing resources, such as guidelines for managing challenges related to cleft lip/palate [48]. In addition, primary health care is often overstretched and underfunded, which affects the quality of support services for all children.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…There is also limited knowledge on feeding practices for small and sick newborns, who are at greater risk for feeding difficulties and malnutrition [46]; limited skills and time for health workers to provide counseling that allows for "trial and error" of different interventions [47]; and limited use of existing resources, such as guidelines for managing challenges related to cleft lip/palate [48]. In addition, primary health care is often overstretched and underfunded, which affects the quality of support services for all children.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Feeding difficulties among children with disabilities are associated with high rates of malnutrition and early life mortality [45]. Previous studies conducted in Rwanda among children born small and sick reported high rates of potential disabilities at ages 2 to 4 years [46] and higher rates of malnutrition among children with feeding difficulties [47], thus additional specialized nutrition interventions are likely required to address these children's needs. Based on this challenge, in 2019, the PDC program integrated early intervention using the Baby Ubuntu model [48], a group participatory early intervention program starting from 6 months for young children with disability and their families.…”
Section: Plos Onementioning
confidence: 99%